Culture and teacher training - Ariane Mieko Himeno Onohara; Ana Carla Fabian Vasselo; José Anderson Santos Cruz; Maria Luiza Mariano (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
In this review, we emphasize the importance of teacher education, responsible for the literacy of children. Thus, it is noteworthy how the appropriation of writing takes place, using and prioritizing facts and events in the daily life of children based on historical-cultural manifestations. Corroborating this aspect, the beginning of the appropriation of the written language of the child. In view of this perspective, considering functional illiteracy in applied didactics.